Assessing the intra- and inter-reader reliability of dynamic ultrasound images in power Doppler ultrasonography. Issue 12 (25th May 2006) - Koski, J M; Saarakkala, S; Helle, M; Hakulinen, U; Heikkinen, J O; Hermunen, H; Balint, P; Bruyn, G A; Filippucci, E; Grassi, W; Iagnocco, A; Luosujärvi, R; et al.
Abstract : Objective: To assess the intra-reader and inter-reader reliabilities of interpreting ultrasonography by several experts using video clips. Method: 99 video clips of healthy and rheumatic joints were recorded and delivered to 17 physician sonographers in two rounds. The intra-reader and inter-reader reliabilities of interpreting the ultrasound results were calculated using a dichotomous system (normal/abnormal) and a graded semiquantitative scoring system. Results: The video reading method worked well. 70% of the readers could classify at least 70% of the cases correctly as normal or abnormal. The distribution of readers answering correctly was wide. The most difficult joints to assess were the elbow, wrist, metacarpophalangeal (MCP) and knee joints. The intra-reader and inter-reader agreements on interpreting dynamic ultrasound images as normal or abnormal, as well as detecting and scoring a Doppler signal were moderate to good (κ = 0.52–0.82). Conclusions: Dynamic image assessment (video clips) can be used as an alternative method in ultrasonography reliability studies. The intra-reader and inter-reader reliabilities of ultrasonography in dynamic image reading are acceptable, but more definitions and training are needed to improve sonographic reproducibility.